Antimalaria Potential and Toxicological Evaluation of Synclisia scabrida (Miers) Ex Oliv Methanol Root Extract in Plasmodium berghei-infected Mice Model - Ogochukwu Ngozi Nwaefulu; John Ihechukwu Nwafor; Daniel Lotanna Ajaghaku; Ngozi Ezinwanne Amuchie; Blessing Akporotu (Biology, Medicine, & Natural Product Chemistry, 2025)
Despite the artemisinin-based combination therapy for malaria treatment, it remains a public health concern globally. Therefore, there is an urgent need for novel antimalarial drugs to arrest this perceived threat to global malaria control. This study aims to investigate the antimalarial potential of S. scabrida (SS) and evaluate its possible effect on haematological and biochemical parameters. Malaria was inoculated in mice using Plasmodium berghei. After 72 h, they were orally treated for four days as follows: Group 1: 10 mL/kg % Dimethyl sulphoxide (DMSO); Group 2: 140 mg/kg Artemether/lumefantrine; Groups 3, 4 and 5: 500, 250, 125 mg/kg SS methanolic extract, respectively. SS methanolic extract significantly reduced parasite density and percentage parasitemia (p < 0.05) at all doses used in the study, non-significantly increased haematological, biochemical parameters and distorted liver architecture; when compared to the negative control. SS methanolic extract exhibited good antimalarial activity against Plasmodium berghei. Lower SS dose did not cause significant changes to the lipid profiles. However, the high dose may not be safe since there were some adverse effects shown on the liver and kidney status. Further studies are warranted to determine the effect of the middle and the lowest doses on the liver and kidney.